On a New Space of Double Sequences - Cenap Duyar; Oğuz Oğur (Journal of Function Spaces and Applications)
We introduce a new space of double sequences related to -absolute convergent double sequence space, combining an Orlicz function and an infinity double matrix. We study some properties of and obtain some inclusion relations involving .